2014
DOI: 10.1590/s0036-46652014000400012
|View full text |Cite
|
Sign up to set email alerts
|

ANTIMICROBIAL DRUG RESISTANCE IN STRAINS OF Escherichia coli ISOLATED FROM FOOD SOURCES

Abstract: A variety of foods and environmental sources harbor bacteria that are resistant to one or more antimicrobial drugs used in medicine and agriculture. Antibiotic resistance in Escherichia coli is of particular concern because it is the most common Gram-negative pathogen in humans. Hence this study was conducted to determine the antibiotic sensitivity pattern of E. coli isolated from different types of food items collected randomly from twelve localities of Hyderabad, India. A total of 150 samples comprising; veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
106
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(139 citation statements)
references
References 29 publications
8
106
2
5
Order By: Relevance
“…1 Among all pathogenic agents causing food-borne diseases, Escherichia coli (E. coli) strains had a significant position. [2][3][4][5][6][7][8] E. coli is a Gram-negative, non-sporulating, flagellated, rod-shaped and facultative anaerobic bacterium of the Enterobacteriaceae family. Shiga (vero) toxin (Stx)-producing E. coli (STEC) is a subdivision of a significant pathogenic group of this bacterium named enterohemorrhagic E. coli (EHEC).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…1 Among all pathogenic agents causing food-borne diseases, Escherichia coli (E. coli) strains had a significant position. [2][3][4][5][6][7][8] E. coli is a Gram-negative, non-sporulating, flagellated, rod-shaped and facultative anaerobic bacterium of the Enterobacteriaceae family. Shiga (vero) toxin (Stx)-producing E. coli (STEC) is a subdivision of a significant pathogenic group of this bacterium named enterohemorrhagic E. coli (EHEC).…”
Section: Introductionmentioning
confidence: 99%
“…Shiga (vero) toxin (Stx)-producing E. coli (STEC) is a subdivision of a significant pathogenic group of this bacterium named enterohemorrhagic E. coli (EHEC). [2][3][4][5][6][7][8] In the other hand, STEC strains are divided into two separate subtypes of EHEC and Attaching and Effacing E. coli (AEEC). EHEC strains are responsible for high morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of authors have reported varying resistance of E. coli isolated from food and other sources to against augmentin (13.3 to 100%), ofloxain (0 to 39.3%), nitrofurantoin (26.17 to 80.0%), gentamicin (0 to 91.37%), ampicillin (22.2 to 100.0%), ciprofloxacin (4.07 to 82.0%) and ceftazidime ((0.0 to 94.02%) (Akond et al, 2009;Oluyege et al, 2009;Adeshina et al, 2012;Ogidi and Oyetayo, 2013;Poonia et al, 2014;Rasheed et al, 2014;Tiamiyu et al, 2015;Boss et al, 2016;Omobije et al, 2016;Sudda et al, 2016).…”
Section: Antibiotic Susceptibility Of Isolated Bacteriamentioning
confidence: 99%